Legal Factors That Affect the Behavior of Teenagers Extorting Drivers - Yunita Wira Baba; Jimmy Pello; Ngongo Dede (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
This study aims to analyze the factors influencing juvenile extortion behavior against drivers in Tasifeto Barat District, Belu Regency, and to examine the efforts to overcome such behavior. This phenomenon has caused public unrest and has the potential to disrupt public order. This research employs an empirical legal method with a qualitative approach, using data collection techniques such as observation, interviews, and documentation involving 15 respondents, including juveniles, local communities, government officials, and police officers. The results indicate that the factors causing extortion behavior consist of internal and external factors. Internal factors include identity crisis and weak self-control among adolescents, while external factors include lack of parental supervision, peer influence, alcohol consumption, and economic conditions. Alcohol consumption is identified as the dominant factor triggering and reinforcing extortion behavior. The efforts to address this issue are carried out through pre-emptive, preventive, and repressive measures. Pre-emptive efforts include legal education and guidance, preventive measures involve patrols and environmental supervision, while repressive actions include law enforcement with a restorative justice approach. However, these efforts have not been fully effective due to the lack of continuous supervision and active involvement of families and communities.